ЗАВХАНЫ САВЫН БАКТЕРИЙН ҮҮСЭЛТЭЙ ВИВИАНИТАТ БА КОЛЛОФАНИТ ФОСФОРИТ, БИОМЕТАЛЛОГЕНИЙ ОНЦЛОГ - Д., Доржнамжаа; Б., Энхбаатар; Г., Алтаншагай (Geological Issues, 2021)
The Zavkhan phosphate basin has been discovered by us as a result of many years’ standing scientific research. This basin locates in the west of Mongolia within the territory of Zavkhan and Govi-Altai provinces inclusive 24000 km2 of the square. In this basin phosphorite or stone of fertility was accumulated approximately 600-500 m. y. ago. The geologic history of the basin gives a possibility to correlate with 80 world phosphate basins. A phosphate-bearing series of deposits in the Ediacaran-Lower Cambrian Tsagaanolom and Bayangol formations has been described. The structure and composition of the Zavkhan phosphate basin are shown to be essentially similar to the phosphate series of the main part of the Khubsugul and Karatau phosphate - bearing basins. In lithology and geochemistry, the Tsagaanolom carbonate formation is distinctly subdivided into dolomite under-phosphoritic, phosphoritic and over-phosphoritic members. Clastic sediments of the Bayangol formation contain stony or black metaphosphoric occurrence with a high content of Al2O3 (up to 15-33%) and also pyritiferous gold, silverbearing mineralization of sulfosalt type. Biogenesis (cyanobacterial mat) of Zavkhan phosphate basin is established as it is exemplified in the Alagiin Davaa, Tsakhir Uul and Khundlun Uul deposits as in the Bayangol and Khevtee Tsakhir Nuruu occurrences within the Khasagt Khairkhan mountain and Zavkhan river area. Bacteria are responsible for the formation of some minerals and elements such as phosphorite, iron, uranium, sulfide, Al, S, Mn, Ta, Nb and can concentrate economically important ores such as coal, oil, gold, also silver.